Sustainable sandwich composites manufactured from recycled carbon fibers, flax fibers/PP skins, and recycled PET core - Jiang, Qihong; Chen, Guiyong; Kumar, Abhideep; Mills, Andrew; Jani, Krutarth; Rajamohan, Vasudevan; Venugopal, Barathan; Rahatekar, Sameer S. (MDPI, 2020)
European union end of life vehicle directive mandates the use of more sustainable/recyclable materials in automotive industries. Thermoplastics matrix-based composites allow recyclability of composites at the end of life; however, their processing technology is more challenging than thermoset composites. Manufacturing process and mechanical testing of sustainable sandwich composite made from sustainable materials: flax, recycled carbon fiber, polypropylene, and recycled PET foam are presented in this article. High pressure compression molding with adhesive thermoplastic polymer film was used for manufacturing sandwich composite skin. The recycled PET foam core was integrated/joined with the skin using a thermoplastics adhesive film. A three-point bending test was conducted to compare the flexural properties. The results show that such sustainable sandwich composites will be an excellent material for truck side panel to operate in adverse wind/storm conditions. The sustainable sandwich composite can potentially be an excellent candidate for the fabrication of light-duty, lightweight, and low-cost engineering structures in automotive industry to meet the EU end of life requirements.
Keywords: sandwich composite; sustainable; mechanical property; mechanical property; flax; recycled carbon fiber; polypropylene